Phage display of cDNA libraries: enrichment of cDNA expression using open reading frame selection - Peggy Ho Faix; Michael A. Burg; Michelle Gonzales; Edward P. Ravey; Andrew Baird; David Larocca (BioTechniques)
Phage display technologies are powerful tools for selecting binding ligands against purified molecular targets, live cells, and organ vasculature. However, the selection of natural ligands using phage display has been limited because of significant problems associated with the display of complex cDNA repertoires. Here we describe the use of cDNA fragmentation and open reading frame (ORF) selection to display a human placental cDNA library on the pIII coat protein of filamentous phage. The library was enriched for ORFs by selecting cDNA-β-lactamase fusion proteins on ampicillin, resulting in a cDNA population having 97% ORFs. The ORF-selected cDNAs were fused to pIII in the phagemid vector, pUCMG4CT-198, and the library was rescued with a pIII-deleted helper phage for multivalent display. The resulting phagemid particle library consisted of 87% ORFs, compared to only 6% ORFs when prepared without ORF selection. Western blot analysis indicated cDNA-pIII fusion protein expression in eight out of nine ORF clones tested, and seven of the ORF encoded peptides were displayed multivalently. The high level of cDNA expression obtained by ORF selection suggests that ORF-enriched phage cDNA libraries prepared by these methods will be useful as functional genomics tools for identifying natural ligands from various source tissues.